Measurement of prompt photon production in √sNN=8.16 TeV p + Pb collisions with ATLAS - Aaboud, Morad; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kolb, Mathis; Kugel, Andreas; S̜ahinsoy, Merve; et al. (Physics letters, 2019)
The inclusive production rates of isolated, prompt photons in p + Pb collisions at √sNN= 8.16 TeV are studied with the ATLAS detector at the Large Hadron Collider using a dataset with an integrated luminosity of 165 nb−1 recorded in 2016. The cross-section and nuclear modification factor RpPb are measured as a function of photon transverse energy from 20 GeV to 550 GeV and in three nucleon–nucleon centre-of-mass pseudorapidity regions, (-2.83, -2.02), (-1.84, 0.91), and (1.09, 1.90). The cross-section and RpPb values are compared with the results of a next-to-leading-order perturbative QCD calculation, with and without nuclear parton distribution function modifications, and with expectations based on a model of the energy loss of partons prior to the hard scattering. The data disfavour a large amount of energy loss and provide new constraints on the parton densities in nuclei.